2011
DOI: 10.1111/j.1468-3083.2011.03992.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral cyclosporin in psoriasis: a systematic review on treatment modalities, risk of kidney toxicity and evidence for use in non‐plaque psoriasis

Abstract: Oral CyA is indicated for patients with plaque psoriasis, pustular psoriasis or erythrodermic psoriasis. The starting dose of 5 mg/kg is associated with a higher degree of clearance. The benefit-risk appears to be better for patients without risk factors for nephrotoxicity: non-obese patients without hypertension and aged below 60. Although CyA is ideally suited for crisis intervention, continuous maintenance treatment with CyA may be envisaged in some patients provided serum creatinin is regularly monitored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 39 publications
2
65
2
2
Order By: Relevance
“…Other studies have shown that obesity is a risk factor for adverse events in patients treated with cyclosporine, especially if other risk factors are present, such as advanced age, concomitant use of nephrotoxic drugs, and hypertension. In such cases, the cyclosporine should be dosed according to ideal weight and not actual weight [64] . Interestingly, adi-posity also appears to affect the effectiveness of treatment with cyclosporine on the severity of psoriasis.…”
Section: Impact Of Obesity On the Treatment Of Psoriasismentioning
confidence: 99%
“…Other studies have shown that obesity is a risk factor for adverse events in patients treated with cyclosporine, especially if other risk factors are present, such as advanced age, concomitant use of nephrotoxic drugs, and hypertension. In such cases, the cyclosporine should be dosed according to ideal weight and not actual weight [64] . Interestingly, adi-posity also appears to affect the effectiveness of treatment with cyclosporine on the severity of psoriasis.…”
Section: Impact Of Obesity On the Treatment Of Psoriasismentioning
confidence: 99%
“…À la dose de 2,5 mg/kg par jour, entre 30 et 60 % des patients vont avoir 75 % ou plus d'amélioration du PASI. À la dose de 5 mg/kg par jour, entre 50 et 90 % des patients vont avoir 75 % d'amélioration du PASI [35]. À l'arrêt du traitement qui peut être brutal, la rechute du psoriasis survient en moyenne en trois à quatre mois [11,36].…”
Section: Ciclosporineunclassified
“…Eighty-nine percent and 50% of subjects with palmoplantar pustulosis and erythrodermic psoriasis obtained satisfactory effects after treatment with cyclosporin. 93 …”
Section: Cyclosporin Amentioning
confidence: 99%